INCREASING ITS STRENGTH BY USING FIBER AND DISPERSE FILLERS IN THE COMPOSITION OF BUILDING GYPSUM - Farxodjon Ibragimov (Web of Journals Publishing, 2024)
Scientific and technical development in the field of construction envisages the use of new and effective construction materials with different characteristics and different functions. In this article, in order to improve the properties of construction gypsum, changes in its strength limits are studied by adding several types of fillers to alabaster.
Keywords: Gypsum, alabaster, filler, dispersion, composite, polyester fibre.